Pengaruh Pengungkapan Korporasi (Corporate Disclosure) terhadap Manajemen Laba dan Kinerja Korporasi - -, Andreas (Universitas Brawijaya, Indonesia, 2009)
As a go public company which half of its shares owned by the public through transactions in stock exchange, the presentation of financial report must qualify conditions as proposed by the authoritative Stock Exchange Committee (Badan Pengawas Pasar Modal). In this research corporate exposure was proved not to have any significant effects on earning management and corporate performance. Besides the lower level of voluntary exposure, stakeholders tend to be suspicious on information and facts presented by go public companies. The following impacts of this distrust was stakeholders do not use corporate disclosure as medium to control managerial activities in term of earning management and corporate performance. Stakeholders’ distrust also implied that corporate exposure had not been able to provide an accurate description regarding what companies really work on. Regulations on corporate exposure is rather a formality than an information provision in financial report.Keywords: corporate exposure, earnings management, corporate performance